The Average Age of Atrioventricular Block Onset in Middle Eastern Patients with Cardiac Rhythm Devices Adjusted for the Overall Young Population: Insights from a Multicenter International Registry - Abdulelah H. Alsaeed; Fawziah Al Kandari; Raed Sweidan; Fayez Bokhari; Ahmed Al Fagih; Abdulmohsen Almusaad; Bander Alghamdi; Amir Abdelwahab; Saad AlHasaniah; Ahmed Hersi; Wael Alqarawi (Ubiquity Press, 2024)
Background: Previous registries have shown a younger average age at presentation with cardiovascular diseases in the Middle East (ME), but no study has examined atrioventricular block (AVB). Moreover, these comparisons are confounded by younger populations in the ME. We sought to describe the average age at presentation with AVB in ME and quantify the effect of being from ME, adjusted for the overall younger population. Methodology: This was a retrospective analysis of PANORAMA registries, which collected data on patients who underwent cardiac rhythm device placement worldwide. Countries with a median population age of ≤30 were considered 'young countries'. Multivariate linear regression was performed to assess the effect of being from ME, adjusted for being from a 'young country', on age at presentation with AVB. Results: The study included 5,259 AVB patients, with 640 (8.2%) from the ME. Mean age at presentation was seven years younger in ME than in other regions (62.9 ± 17.8 vs. 70 ± 14.1, P < 0.001). Being from a 'young country' was associated with 5.6 years younger age at presentation (95%CI -6.5--4.6), whereas being from ME was associated with 3.1 years younger age at presentation (95%CI -4.5--1.8), (P < 0.001 for both). Conclusion: The average age at presentation with AVB in the ME is seven years younger than in other regions. While this is mostly driven by the overall younger population, being from the ME appears to be independently associated with younger age. Determinants of the earlier presentation in ME need to be assessed, and care should be taken when applying international recommendations.